2020
DOI: 10.5114/aoms.2019.83883
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory sinus arrhythmia is reduced after pulmonary vein isolation in patients with paroxysmal atrial fibrillation

Abstract: Introduction: Respiratory sinus arrhythmia (RSA) describes heart rate (HR) changes in synchrony with respiration. It is relevant for exercise capacity and mechanistically linked with the cardiac autonomic nervous system. After pulmonary vein isolation (PVI), the current therapy of choice for patients with paroxysmal atrial fibrillation (AF), the cardiac vagal tone is often diminished. We hypothesized that RSA is modulated by PVI in patients with paroxysmal AF. Material and methods: Respiratory sinus arrhythmia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…RSA is a physiological phenomenon resulting from the regulation of the cardiac system by the vagus nerve and could be used as an indicator of vagal activity (Porges, 2007;Lubocka and Sabiniewicz, 2021). It has been found that decreased RSA is associated with reduced cardiac vagal activity in patients with paroxysmal atrial fibrillation after undergoing pulmonary vein isolation (Jungen et al, 2019). Increasing the biofeedback training of RSA can effectively enhance vagal regulation (Munafò et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…RSA is a physiological phenomenon resulting from the regulation of the cardiac system by the vagus nerve and could be used as an indicator of vagal activity (Porges, 2007;Lubocka and Sabiniewicz, 2021). It has been found that decreased RSA is associated with reduced cardiac vagal activity in patients with paroxysmal atrial fibrillation after undergoing pulmonary vein isolation (Jungen et al, 2019). Increasing the biofeedback training of RSA can effectively enhance vagal regulation (Munafò et al, 2016).…”
Section: Discussionmentioning
confidence: 99%